Effects of 12 crops associated with plantain on arthropods trophic groups and Cosmopolites sordidus abundance - (:unkn) unknown (My University, 2024)
The control of pests and diseases is one of the main challenges of sustainable agriculture. Plantains, with an annual production of nearly 12 million tons, are a significant staple food crop in West and Central Africa, as well as in Central America. Cosmopolites sordidus is the major pests for plantains and is present in all production areas. This study assessed how the traits and associated agricultural practices of 12 crops, usually associated with plantains in Cameroun, affected the arthropods trophic network and C. sordidus abundance. The abundance and the diversity of arthropods in experimental plots associating plantains with each of the 12 tested crops were measured. Each associated crop was described by a unique profile of traits and agricultural practices. This 'trait' approach allowed linking the plant characteristics to the abundance of arthropods from different trophic groups. Structural equation modelling was used to analyse the interactions between associated crops traits, their associated agricultural practices and the abundance of main trophic groups. The highest abundance of C. sordidus was observed in plots with Ananas comosus and Xanthosoma sagittifolium as associated crops. These plots also had the lowest abundance of omnivores and predators. In contrast, plots with the lowest abundance of C. sordidus were those with weeds and Vigna unguiculata, where more omnivores and predators were observed. Grouping associated crops by their traits and agricultural practices allowed for drawing conclusions on a wider range than the set of plants tested. For instance, this study showed that plants from the higher strata tend to decrease ground-dwelling predators. The ideal crop traits and agricultural practices to maximize the regulation of C. sordidus should not be obtained by a single species of crop but rather by a community of associated crops.
Keywords: African Research